Prof. Angelo Vivian: Prispevek k biografiji pozabljenega judaista slovenskih korenin = Prof. Angelo Vivian: A Contribution to the Biography of a Forgotten Expert for Judaism with Slovenian Roots - Podbersič, Renato (Edinost in dialog, 2021)
Professor Angelo Vivian Ph.D. (1942-1991), the son of an Italian policeman from Veneto region and a Slovene mother from Idrija, a Catholic priest, Judaist, university pro-fessor, translator, editor and publicist, is almost unknown to the Slovene public today. He re-ceived his doctorate in theology and philology from the Universities of Ljubljana (1970) and Florence (1974). As a scientist he worked at the Universities of Florence and Pisa, and since 1986 at the Martin Buber Institute for Jewish studies and the University of Cologne. For many years he had also successfully led the scientifically oriented Italian Association for the Study of Judaism. His research has been published in many languages, including Slovene, most notably in the scientific journal Egitto e Vicino Oriente from Pisa. At the various professional institutions, he searched for the remains of Hebrew inscriptions and books. With his excel-lent palaeographic knowledge, he was able to discover a number of texts important to our circumstances, which he processed and published in numerous articles. He died a sudden death during an excursion to Poland. His rich material, kept by his youngest brother Pietro, is located in Calcinaia, Tuscany, and is still awaiting proper evaluation.